THE COMMUNITY PERCEPTION TO GOOD GOVERNANCE IMPLEMENTATION OF VILLAGE FUNDS IN BANTUL REGENCY - Wiyono, Gendro; Susilowati, Fanda (Journal of Governance and Public Policy, 2018)
This study aims to determine the perception of the community on the implementation of Village Fund Allocation that is used for the Implementation of Village Governance, Village Development, empowerment of rural communities, and Community Activities. with the influence of moderation good governance. The purpose of village fund allocation in principle to improve the welfare and equity of village development through improving public services in the village, promoting the village economy, overcoming the inter-village development gap and strengthening the village community as the subject of development. This is in accordance with the substance of Village Law No. 6/2014 to grant greater autonomy to the village in order to become self-reliant. currently there are still many parties who do not understand the use of village funds. There needs to be an appropriate and understandable media for village community can see and know the village government has done in the use of the village budget. This study uses secondary data collected from village administration, while primary data is collected from Bantul village community. Data analysis used Structural Equation Modeling based variance with the help SmartPLS software. The results showed that the simultaneous administration of village funding for all programs has a positive and significant impact on the perception of the village community perception, while the program partially for each funding does not significantly affect. Good governance as an independent variable significantly influences the perceptions of village communities, but the role of Â Governance for the implementation of each partial funding program has no significant effect on community village perception.